Polyoxometalate-based Gemini ionic catalysts for selective oxidation of benzyl alcohol with hydrogen peroxide in water. Issue 17 (15th August 2018) - Hao, Pengbo; Zhang, Mingjie; Zhang, Wei; Tang, Zhiyang; Luo, Ni; Tan, Rong; Yin, Donghong
Abstract : Polyoxometalate-based Gemini ionic hybrids with inherent phase transfer capability are highly efficient and recyclable catalysts in the selective oxidation of alcohols with H2 O2 in water. Abstract : Keggin-type phosphotungstic acid (H3 PW12 O40, HPW)-based di-imidazolium ionic liquid (IL) hybrids were prepared by exchanging the protons of HPW with PEG-bridged di-imidazolium cations in water. Characterization results suggested that intact Keggin-type [PW12 O40 ] 3− anions were incorporated with various PEG-modified di-imidazolium cations through ionic interaction, giving PW-based ionic catalysts with a Gemini structure. PEG-bridged di-imidazolium cations could not only fine-tune the redox properties of PW anions but also enhanced the compatibility of the catalyst in the aqueous system, which in turn improved its catalytic performance. Furthermore, combination of double catalytic sites into a single molecule enforced an intramolecular, cooperative reaction pathway resulting in a further enhanced reaction rate and higher selectivity in the selective oxidation of benzyl alcohol with H2 O2 in water. More importantly, the di-imidazolium IL cations imparted a reaction controlled phase transfer function to the PW hybrids. The catalysts were thus precipitated from the aqueous system upon consumption of H2 O2 and could be reused several times without loss of activity and selectivity.